2022
DOI: 10.1186/s40813-022-00277-8
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of African swine fever virus on porous and non-porous fomites at environmental temperatures

Abstract: Background African swine fever (ASF) is a lethal contagious disease affecting both domestic pigs and wild boars. Even though it is a non-zoonotic disease, ASF causes economic loss in swine industries across continents. ASF control and eradication are almost impossible since effective vaccines and direct antiviral treatment are not available. The persistence of ASFV on fomites plays an important role in the indirect transmission of ASFV to pigs encountering ASFV-contaminated fomites. ASFV persis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
3
7
0
Order By: Relevance
“…Temperature and humidity can affect the survival and transmission rate of viruses in the environment. Persistence of dried infectious ASFV on paper are significantly the longest at lower environmental temperatures whereas that of dried infectious ASFV on paper is significantly the shortest at higher environmental temperature, but that limited by the type of pollutants and ambient humidity 38 . ASFV in feces could remain infectious longer in 4 °C than 37 °C 39 .…”
Section: Discussionmentioning
confidence: 94%
“…Temperature and humidity can affect the survival and transmission rate of viruses in the environment. Persistence of dried infectious ASFV on paper are significantly the longest at lower environmental temperatures whereas that of dried infectious ASFV on paper is significantly the shortest at higher environmental temperature, but that limited by the type of pollutants and ambient humidity 38 . ASFV in feces could remain infectious longer in 4 °C than 37 °C 39 .…”
Section: Discussionmentioning
confidence: 94%
“…The estimated survival time of infectious ASFV is affected by several environmental factors, including pH, temperature, type of fomite, light exposure, and the presence of viral aggregates ( Arzumanyan et al, 2021 ; Nuanualsuwan et al, 2022 ). Previous studies have evaluated the persistence of infectious ASFV on different materials under ambient temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…ASFV survived longer in pork (18–83 days) than in tissues (9–17 days) and plasma (14 days) at room temperature ( Petrini et al, 2019 ; Mazur-Panasiuk and Wozniakowski, 2020 ; Fischer et al, 2021 ). Additionally, porous materials, such as rubber and cellulose paper, supported ASFV viability for longer periods (14–22 days) than non-porous materials, like glass and metal (11–17 days) at 25°C ( Nuanualsuwan et al, 2022 ). Infectious ASFV has also been detected in sterile sand for at least 3 weeks, beach sand for up to 2 weeks, yard soil for 1 week, and swamp soil for 3 days ( Carlson et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Infected carcasses are a potential source of environmental contamination, particularly the soil under the carcass and other objects around [e.g., ( 25 , 26 )]. The results of soil contamination testing in this study showed that viral DNA was detectable in soil contaminated with ASFV-infected carcasses, long after the carcasses were removed.…”
Section: Discussionmentioning
confidence: 99%